Contrast induced nephropathy - cardiologist perspective - Sharma, Sanjib Kumar; Dubey, Laxman; Guruprasad, Sogunuru; Subramanyam, Gangapatnam (Nepalese Heart Journal, 2014)
Use of contrast media for cardiovascular intervention is associated with risk of contrast induced nephropathy. Contrast induced nephropathy is associated with increased morbidity, prolonged hospitalization, potential need for dialysis and increased mortality rate. Although the consequences of contrast induced nephropathy are well known, the prospective identification of patient at risk for nephropathy has been inconsistent. The mechanism of contrast induced nephropathy is complex and not fully understood. Direct tubular toxicity and disturbances of renal hemodynamic with altered glomerular filtration and renal medullary ischemia are the most important path-physiological mechanism. Prevention of contrast induced nephropathy is address in numerous studies. The most attractive agents include hydration, N-acetylcysteine, and infusion of sodium bicarbonate. This review focuses on the definition, pathophysiology and prevention of contrast induced nephropathy. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 30-37 DOI: http://dx.doi.org/10.3126/njh.v10i1.9745